Celowość stosowania benchmarkingu, reengineeringu oraz organizacji sieciowych w procesie budowania przewagi konkurencyjnej przedsiębiorstwa (na przykładzie sektora telefonii stacjonarnej) - Jeżak, Jan; Kozłowski, Remigiusz (Advisability of Using Benchmarking, Reengineering and Net Organizations in the Process of Building Enterprise Competitive Superiority (Based on the Fixed Telecommunication Sector), 2006)
The article concerns the advisability of usage benchmarking, reengineering and net organization by the fixed telecommunications operators in the process of creating the competitive advantage. The results of empirical research that presents the frequency of using this methods and benefits of implement this concepts.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1104, s. 430-437